(untitled) (Bangladesh Journal of Botany, 2022)
In the present investigation horticultural performances of field grown somaclones and gamma irradiated strawberry were studied. The somaclones performed better with regard to vegetative and reproductive characters while axillary buds irradiated with lower dose of gamma rays (10 and 30 Gy) were more vigorous in terms of number of leaves and petiole length. Whereasaxillary buds irradiated with higher dose of gamma rays (50 and 60 Gy) showed abnormal fruit development, reduced growth, small leaf area and fruit size. A total of six variants were obtained on screening the somaclones and irradiated plantlets on the basis of phenotypic characters, fruiting characters and Single Sequence Repeat (SSR) markers. The frequency of variants was higher (3.22%) in soamclones than in irradiated plants (2.75%) obtained from axillary buds. These finding would be helpful in providing a powerful technological tool for the improvement of clonally propagated crops. Bangladesh J. Bot. 51(3): 555-563, 2022 (September)